A case of abomasal impaction in a captive giraffe (Giraffa camelopardalis) - D. V. Gradwell (Koedoe: African Protected Area Conservation and Science, 1976)
A male giraffe calf was brought into the experimental pens at Skukuza after being found on its own in poor condition in the Kruger National Park, Republic of South Africa. The mother of the calf could not be traced.